Plasma cfDNA as a potential treatment monitoring and prognostic index in patients withnon-small cell lung cancer - Chen, Nan; Li, Gaofeng; Li, Heng; Xiang, Xudong; Guo, Gang; Ma, Qianli; Zhang, Ying (Cellular and Molecular Biology, 2020)
The purpose of this study was to investigate the potential of cell-free DNA (cfDNA) as a prognostic factor for non-small cell lung cancer (NSCLC). Patients with NSCLC (n = 154) treated with gefitinib were recruited over a 5-year period for this study, and served as the observation group (79 males and 75 females, mean age = 53.74 ± 10.86 years). The control group (normal healthy individuals) consisted of 30 males and 22 females, aged 44 – 64 years (mean age = 54.12 ± 9.83 years). The follow-up lasted 5 years, or until the patient relapsed and died. The plasma level of cfDNA was determined in patients 1 day before treatment, 3 days after treatment, and on the 28th day of treatment.Based on the cfDNA expression level, NSCLC patients were subdivided into high-expression and low-expression groups, and differences in survival were compared. Univariate and multivariate analyses were performed on factors affecting patients survival using COX. Total effectiveness was significantly higher in observation group (49.35%) than in control group (13.95 %) (p<0.05). The extent of disease control wasalso significantly higher in the observation group (93.51 %) than in control group (p<0.05). Plasma cfDNA level of NSCLCpatients was significantly higher than that of control group before treatment, but was significantly and time-dependently reduced after gefitinib treatment (p<0.05). Cell-free DNA (cfDNA) level increased with severity of disease (p<0.05). Patients in cfDNA low-expression group had significantly higher chances of survival than those in the high-expression group (p<0.05). The results of Cox multivariate analysis showed that pathological severity and cfDNA concentration were independent factors affecting prognosis of NSCLC (p<0.05). Plasma cfDNA is a potential prognostic index in patients with NSCLC.